Identifying English Teachers' Emotional Labour While Teaching Speaking in the EFL Class: A Narrative Inquiry - Aqnia, Nadhirdya Fasya; Ariani, Musli; Rofiq, Annur (EFL Education Journal, 2024)
The use of emotional labour in teachers is of course very much needed both outside the classroom and in the classroom. Emotions can be divided into positive and negative emotions. However, not many studies have conducted the range of these emotions in emotional labour and various kinds of regulation. This study used narrative inquiry that aimed to identify English teachers’ emotional labour while teaching speaking in EFL class. The research data were collected through interview and then analyzed by using thematic analysis. The research found that the English teachers at one of the senior high school in Mojokerto felt both negative and positive emotions when teaching speaking. However, with the negative emotions that arise, this was easily overcome by regulating it. The regulating carried out by the teachers are social interaction and the use mindset. With those regulations, teachers easily changed their negative emotions into positive emotions. The same went for positive emotions. In this study, some positive emotions need to be regulated and some do not.